2017
DOI: 10.1002/ceat.201600600
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the Velocity Gradients in a Vessel Agitated by a Rushton Turbine

Abstract: Scaling of fluctuation velocity gradients was investigated in a vessel agitated by a Rushton turbine. By using turbulence spectrum analysis, it was derived that, for high Reynolds numbers, the squared dimensionless local fluctuation velocity gradient is proportional to the squared impeller Reynolds number. This theoretical prediction was tested on experimental data in the range Re = 50 000 – 110 556. The calculated isotropy ratios are independent of the impeller Reynolds number, and their inter‐ratios depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nevertheless, many PIV studies do not take the spatial resolution effect into account. In our previous work , we found that the fluctuation velocity gradients are also affected by PIV resolution. The recording time is another crucial factor that influences the relevance and accuracy of measured data.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many PIV studies do not take the spatial resolution effect into account. In our previous work , we found that the fluctuation velocity gradients are also affected by PIV resolution. The recording time is another crucial factor that influences the relevance and accuracy of measured data.…”
Section: Introductionmentioning
confidence: 99%